Hemophagocytic lymphohistiocytosis secondary to histoplasmosis: A case report in a patient with AIDS and recent SARS-CoV-2 infection and minireview - Luca Pipitò; Alice Annalisa Medaglia; Marcello Trizzino; Alessandro Mancuso; Bianca Catania; Salvatrice Mancuso; Cinzia Calà; Ada Maria Florena; Antonio Cascio (Heliyon, 2023)
Here, we describe the case of a naïve HIV late presenter female African patient with progressive disseminated histoplasmosis and a severe life-threatening clinical picture in a non-endemic area. She had not visited Africa in the past decade. She developed a reactive hemophagocytic lymphohistiocytosis and an acute psychiatric disorder. Histoplasmosis was diagnosed after two bone marrow biopsies. Therapy with liposomal amphotericin B resulted in rapid and progressive improvements in blood examinations and clinical conditions, including the disappearance of psychiatric disorders. The characteristics of our case were compared with those of all other cases of hemophagocytic syndrome secondary to histoplasmosis in HIV-positive patients reported in PubMed. In conclusion, clinicians outside endemic areas should evaluate histoplasmosis as a cause of severe clinical picture, especially in a patient with a travel history to an endemic area, even after many years, considering the possible reactivation of latent infection.